1939
DOI: 10.1021/j150396a013
|View full text |Cite
|
Sign up to set email alerts
|

The Phase Rule Behavior of Concentrated Aqueous Systems of a Typical Colloidal Electrolyte: Sodium Oleate.

Abstract: This paper is in the nature of a preliminary report on the phase rule behavior of sodium oleate and water, there being no previous study in the literature. The purpose of this investigation was to determine whether the sequence of phases intermediate between crystalline curd fiber phase and isotropic liquid, recently discovered (17,18) in the case of anhydrous sodium palmitate also exists for sodium oleate, and, if so, to determine the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
3

Year Published

1956
1956
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 12 publications
4
29
3
Order By: Relevance
“…The Krafft discontinuity is slightly changed with increasing the surfactant composition. This result is in agreement with studies by Vold [10], where this discontinuity was identified as the temperature at which the last trace of opaque solid disappears by heating.…”
Section: Phase Diagramsupporting
confidence: 93%
See 1 more Smart Citation
“…The Krafft discontinuity is slightly changed with increasing the surfactant composition. This result is in agreement with studies by Vold [10], where this discontinuity was identified as the temperature at which the last trace of opaque solid disappears by heating.…”
Section: Phase Diagramsupporting
confidence: 93%
“…The phase diagram of NaO in water was the subject of two dated studies by Vold [10] and Luzzati et al [11], respectively. They study the presence of an isotropic liquid region and an hexagonal liquid crystalline phase, lying within an accessible experimental temperature-composition interval.…”
Section: Introductionmentioning
confidence: 99%
“…While the sample containing only NaO is transparent, which results from the micellar phase reported in the literature [18,19], the remaining samples exhibit bluish color, which is usually related to the existence of vesicles.…”
Section: Methodsmentioning
confidence: 89%
“…These 2 amphiphilic molecules form different structures in water. While the critical packing parameter (CPP) of MO exceeds one, NaO forms normal micelles [18,19]. In the dilute corner, spontaneously formed vesicles with long-term stability are found (for at least 1 year) [15].…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that the obvious influence of the existence of C=C bond in sodium oleate (NaO) on the mixture properties of cationic surfactants and NaO is different from the influences of cationic surfactants and NaS [12,13] . The phase boundaries in ternary systems of NaO, compared with other soap, were reported as early as in 1939 [14,15] . However, the comparative study on the salt-free cationic surfactants mixed with alkyl fatty acids with a double carbon bond (C=C) and the saturation hydrophobic alkyl chain has not been reported in literature [9] .…”
Section: Cationic Base Surfactant Tetradecyltrimethylammonium Hydroxmentioning
confidence: 99%